INDIGENOUS KNOWLEDGE AND DISASTER RESILIENCE FOR CHILDREN: READING SMONG IN SELECTED LITERACY CLOUD SHORT STORIES - Anna Anganita Theresia Latumeten; Ulum Janah (Prologue: Journal on Language and Literature, 2024)
This study explores the integration of indigenous knowledge into children’s literature as a means of promoting disaster resilience among young readers. Through the lens of ecocriticism and descriptive qualitative research methodology, the study investigates the portrayal of smong, a form of indigenous knowledge from the Simeulue region of Indonesia, in two selected Literacy Cloud short stories: “Tsunami” by Yovita Siswanti and “Smong, the Dragon” by Maya Lestari. The analysis reveals how these stories effectively incorporate smong as a repository of local wisdom and resilience lessons in the face of natural disasters. Encouraging initiatives to incorporate more themes of indigenous knowledge into children's literature is crucial for promoting cultural preservation. In addition, integrating indigenous knowledge—particularly those with content related to disaster resilience—is valuable to empower children in disaster-prone areas. Overall, the study highlights the potential of children’s literature and digital platforms for education in fostering a harmonious relationship between humanity and the natural world amidst the challenges of environmental sustainability and possibilities of natural disasters.